MYOFUNCTIONAL THERAPY IN ANTERIOR DEEP BITE AND TMD PATIENT-CASE REPORT - Srbinoska, Daniela; Trpevska, Vesna; Radeva, Maja; Mijoska, Aneta (Journal of Morphological Sciences, 2021)
Deep bite is perhaps one of the most common dental malocclusions seen in children as well as in adults and is very demanding to be treated successfully. A skeletal or dental overbite is caused by genetic or environmental factors, or a combination of both. The ideal overbite in a normal occlusion may range from 2 to 4 mm. Mild deep bite typically requires no correction, unless correction for aesthetic reasons. Severe overbite, considered as a clinical problem may affect the temporomandibular joint, causes periodontal problems and tooth wearing, as well as traumatizing the incisive papilla or interfering with mastication function. Anterior deep bite could be caused by overeruption of upper and/or lower incisors or undereruption of posterior teeth. Correction of deep overbite has always been challenging to orthodontists, especially in adult cases. There are different modalities in orthodontic treatment of this malocclusion. Deep bite correction can be treated with intrusion of incisors, extrusion of posterior teeth, combination of both, and orthognathic surgical modality. The aim of this case report was to present treatment protocol for an adult patient with skeletal deep bite, Class II Division 1 malocclusion and temporomandibular disorder (TMD) managed with conventional orthodontics therapy combined with orofacial myofunctional exercises. The modality of exercise therapy included improvement of proprioception, tonicity and mobility, working with the facial and cervical musculature, as well as with stomatognathic functions - respiration, mastication, deglutition and speech. The most important thing is to aid long-term retention. Keywords : anterior deep bite, TMD, myofunctional therapy. https://doi.org/10.55302/JMS2143033s